Pancasila Values in the Study of Corruption Cases in Indonesia - Aninda, Catleya Azka (Universitas Negeri Semarang, 2017)
Pancasila is the basis of the Indonesian state which is used as the guideline for the Indonesian state. Pancasila means five principles or five principles. The relationship between corruption and Pancasila is that corruption is behavior that violates Pancasila as the basis of the Indonesian state, therefore corruption must be subject to appropriate sanctions or punishments for using people’s money arbitrarily (personal interests). Pancasila in Indonesia plays an important role in people's lives, starting from the rights and obligations regulated in Pancasila.